2006
DOI: 10.4103/0019-5545.31579
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of conduct disorder in schoolchildren of Kanke

Abstract: Background:Prevalence estimates of conduct disorder, one of the most frequently diagnosed psychiatric conditions in children, vary widely from 0.2% to 8.7%.Aim:To find out the prevalence of conduct disorder and its DSM-IV subtypes and comorbid attention deficit hyperactivity disorder (ADHD) in 4 schools of Kanke block among students of classes V to X.Methods:A total of 240 students, selected by stratified random sampling, were subjected to the Schedule for Affective Disorders and Schizophrenia for School Age C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
(35 reference statements)
8
23
0
1
Order By: Relevance
“…This result confirmed the findings of previous studies such as (Pratt et al, 2003;Sarkhel, Sinha, Arora, & DeSarkar, 2006;Ziaodini & Shafizadeh, 2005) that the prevalence of CD among boys is more than girls. Ziaodini and Shafizadeh (2005) studied the epidemiology of Conduct Disorder in Sirjan/Iran between 18726 students in elementary schools between 7 to 11 years old.…”
Section: Studies In Iran Among Children With Conduct Disordersupporting
confidence: 92%
See 1 more Smart Citation
“…This result confirmed the findings of previous studies such as (Pratt et al, 2003;Sarkhel, Sinha, Arora, & DeSarkar, 2006;Ziaodini & Shafizadeh, 2005) that the prevalence of CD among boys is more than girls. Ziaodini and Shafizadeh (2005) studied the epidemiology of Conduct Disorder in Sirjan/Iran between 18726 students in elementary schools between 7 to 11 years old.…”
Section: Studies In Iran Among Children With Conduct Disordersupporting
confidence: 92%
“…Sarkhel, Sinha, Arora, and DeSarkar (2006) implemented a study in India for the prevalence of CD and reported as 4.58% of boys and 4.5% of girls with CD. This study stated that 36% of these children suffer from CD with mild severity and 64% with moderate severity.…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of boys were a little higher than in other studies. [ 7 12 ] The reason for this could be due to the difference in the clinic and community population and the service seeking attitude.…”
Section: Discussionmentioning
confidence: 99%
“…This supports previous studies that suggested high prevalence of behavioural issues among Iraqi school children (Al‐Obaidi & Ali, ) and by other studies from developing countries. In the United Arab Emirate, for example, 11.8% of children age 6–18 were reported to have behavioural problems (Eapen, Swadi, Sabri, & Abou‐Saleh, ), and adolescent conduct and behavioural issues were similarly prevalent in studies in India and Nigeria (Sarkhel, Sinha, Arora, & DeSarkar, ; Akpan, Ojinnak, & Ekanem, ). Our teacher participants also observed a substantial problem with schoolchildren feeling stressed or angry much of the time, suggesting a concerning level of untreated child mental health problems.…”
Section: Discussionmentioning
confidence: 99%